PENGARUH ABU SABUT KELAPA DAN PUPUK UREA TERHADAP PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE-NURSERY PADA MEDIA GAMBUT - Bambang Hermanto; Sulhaswardi (UIR Press, 2024)
This study aims to investigate the effects of coconut coir ash and urea on the growth of oil palm seedlings in a pre-nursery setting utilizing peat media. Conducted at the experimental farm of the Faculty of Agriculture at Riau Islamic University, located at Jalan Kaharuddin Nasution KM 11 No. 113, Air Winter Village, Bukit Raya District, Pekanbaru City, the research spanned from November 2022 to February 2023. A factorial completely randomized design (CRD) was employed, featuring two variables: the dosage of coconut fiber ash (0, 7.037, 14.075, and 21.113 g per polybag) and the dosage of urea fertilizer (0, 0.105, 0.210, and 0.315 g per polybag). This setup resulted in 48 experimental units, comprised of 16 treatment combinations, each replicated three times. The parameters evaluated included pH of the peat, plant height, number of fronds per plant, tuber diameter, wet weight, dry weight, and root volume. Statistical analysis was performed on the collected data, followed by a 5% Bonferroni-adjusted multiple comparisons test. Findings from the study revealed that the combination of coconut fiber ash and urea did not significantly affect any characteristics of the oil palm seedlings. However, coconut fiber ash emerged as a significant factor for all measured parameters, with the optimal treatment identified at a rate of 21.113 g per polybag. Similarly, urea demonstrated significance across all evaluated parameters, with the most effective dosage being 0.315 g per polybag.